The riddle of holiday house - Blyton, Enid; Baverstock, Gillian (Award Publications Worksop, England, 2014)
The Riddle of Holiday House by Enid Blyton is a mystery novel centered around two siblings, Nick and Katie, who spend their vacation at a large, eerie mansion called Holiday House. While exploring, they encounter strange happenings and mysterious characters, including odd noises, hidden rooms, and cryptic messages. Intrigued by the secrets of the house, the siblings set out to solve the riddle behind its strange occurrences. Along the way, they uncover a hidden treasure and a plot involving deceit and greed. The story combines elements of suspense, adventure, and teamwork as the children work together to unravel the mystery.